EFEK PEMUASAAN DAN PAKAN FERMENTASI TERHADAP LAJU PERTUMBUHAN DAN FEED CONVERTION RATIO IKAN NILA (Oreochromis niloticus) - Suardi Laheng; Fiansi Fiansi; Ambarwati Ambarwati (Universitas Sriwijaya, 2020)
The main fish farming activities at the enlargement stage require a feed cost of around 60% of the total production cost. Efforts that can be made to reduce the cost of feed are through the starvation and fermentation of feed. This study uses a Completely Randomized Design (CRD) which is 3 treatments and 3 replications. The treatments tried were treatment A = protein feed 31-33% without fermentation (daily feeding), treatment B = protein feed 21-23% fermentation,, (daily feeding), treatment C = protein feed 21-23% fermentation, (1 day starvation 1 day re-feeding), treatment D = protein feed 21-23% fermentation, (1 day starvation 2 days re-feeding), E treatment = protein feed 21-23% fermentation, n (1 day starvation 3 days re-feeding). The study was conducted in a walled pond which was sealed using a net (50 x 50 x 100 cm3), feeding 3 times a day. The results showed that the treatment E effectively suppressed the FCR value and offset the daily growth rate of Treatment A. In addition, treatment E has the same FCR value as treatments B, C, D but treatment E has a higher daily growth rate.Keywords: starvation, fermentation, growth, FCR